THE IMPLEMENTATION OF THE RIGHT TO EDUCATION IN SOUTH AFRICA AND NIGERIA (PART 2) - Elijah Adewale Taiwo; Avinash Govindjee (Obiter, 2021)
This is the concluding part of the two articles dealing with the implementation of the right to education in South Africa and Nigeria. While the first article examines legislative measures put in place towards implementing the right to education, this follow-up article examines the non-legislative measures, that is, administrative and other measures. The article also identifies some problems such as inadequate planning, poor implementation of policies, inadequate resources and commitments as the prime factors hampering the effective implementation of the right to education in the two countries. It concludes by submitting that solving these problems and making the right to an education realizable call for a renewed government commitment and investment of appropriate human and financial resources on education.